Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/coatings5030465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Photocatalytic Properties of Portland Cement Blended with Titanium Oxynitride (TiO2−xNy) Nanoparticles

Abstract: Photocatalytic activity of Portland cement pastes blended with nanoparticles of titanium oxynitride (TiO2−xNy) was studied. Samples with different percentages of TiO2−xNy (0.0%, 0.5%, 1%, 3%) and TiO2 (1%, 3%) were evaluated in order to study their self-cleaning properties. The presence of nitrogen in the tetragonal structure of TiO2 was evidenced by X-ray diffraction (XRD) as a shift of the peaks in the 2θ axis. The samples were prepared with a water/cement ratio of 0.5 and a concentration of Rhodamine B of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…TiO 2 is shown as three crystalline structures: rutile, anatase, and brookite, being the first two forms as the most suitable for photocatalysis [23]. The photooxidation of organic matter has been evaluated in different construction materials such as bricks [24], stone [18,25], and mortars based in different binders [19,26,27]. Most of the research focused on self-cleaning has been made using the TiO 2 product as a coating [21,26].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is shown as three crystalline structures: rutile, anatase, and brookite, being the first two forms as the most suitable for photocatalysis [23]. The photooxidation of organic matter has been evaluated in different construction materials such as bricks [24], stone [18,25], and mortars based in different binders [19,26,27]. Most of the research focused on self-cleaning has been made using the TiO 2 product as a coating [21,26].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that sunlight shows 60% of visible photons in comparison with a mere 4.5% of UV photons. So far, just very few works have been devoted to the study of these doped photocatalysts when incorporated into cementitious matrices [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the low concentration region illustrated in Figure 6 (0.1-1.0 g/L of TiO 2 ) the direct linear dependence of the removal percentage with the photocatalyst concentration is observed. On the other hand it was found that for relatively high concentrations (2.0-2.5 g/L of TiO 2 ) this behavior continues; Whereas for the highest concentration, which corresponds to 3.0 g/L of TiO 2 , the removal percentage shows a tendency to decrease due to an excessive opacity of the solution which prevents titanium dioxide from the innermost part of the reactor being illuminated by directly affecting the reaction rate when the photocatalyst is in suspension Of shielding) 19 . Figure 7 shows the decrease in Cr (VI) concentration for different initial concentrations.…”
Section: Effects Of Tio 2 Dosage (Cr +6 )mentioning
confidence: 99%